The Behaviour of Various Platelet Function Tests During Long-Term Prostacyclin Infusion in Patients with Peripheral Vascular Disease - Sinzinger, H; Horsch, A K; Silberbauer, K (Thrombosis and Haemostasis, 1983)
In 20 patients with peripheral vascular disease treated with prostacyclin (5 ng/kg/min) we observed a significant activation of platelet function as measured by platelet proteins, ADP- induced aggregation platelet sensitivity and platelet count. Only the platelet survival was significantly prolonged by the treatment.
Keywords: Prostacyclin treatment; Platelet survival; Platelet proteins; ADP-induced aggregation; Platelet sensitivity antiaggregatory prostaglandins; Peripheral vascular disease